Tumor microenvironment in giant cell tumor of bone: evaluation of PD-L1 expression and SIRPα infiltration after denosumab treatment - Yu Toda (Nature Portfolio, 2021)
Abstract Giant cell tumor of bone (GCTB) is an intermediate malignant bone tumor that is locally aggressive and rarely metastasizes. Denosumab, which is a receptor activator of nuclear factor kappa B ligand (RANKL) inhibitor, can be used to treat GCTB. We focused on potential immunotherapy for GCTB and investigated the tumor microenvironment of GCTB. Programmed death-ligand 1 (PD-L1) and indoleamine 2,3-dioxygenase 1 (IDO1) expression and signal-regulatory protein alpha (SIRPα), forkhead box P3 (FOXP3), and cluster of differentiation 8 (CD8) infiltration were assessed by immunohistochemical studies of 137 tumor tissues from 96 patients. Of the naive primary specimens, 28% exhibited PD-L1 expression and 39% exhibited IDO1 expression. There was significantly more SIRPα+, FOXP3+, and CD8+ cell infiltration in PD-L1- and IDO1-positive tumors than in PD-L1- and IDO1-negative tumors. The frequency of PD-L1 expression and SIRPα+ cell infiltration in recurrent lesions treated with denosumab was significantly higher than in primary lesions and recurrent lesions not treated with denosumab. PD-L1 expression and higher SIRPα+ cell infiltration were significantly correlated with shorter recurrence-free survival. PD-L1 and SIRPα immune checkpoint inhibitors may provide clinical benefit in GCTB patients with recurrent lesions after denosumab therapy.